2017
DOI: 10.1093/geronb/gbx055
|View full text |Cite
|
Sign up to set email alerts
|

The Role of General and Daily Control Beliefs for Affective Stressor-Reactivity Across Adulthood and Old Age

Abstract: Mixed evidence of age differences across general and daily control beliefs highlights how within-person processes may differentially contribute to well-being as individuals accommodate age-related strengths and vulnerabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 53 publications
(60 reference statements)
2
30
0
Order By: Relevance
“…As a consequence, they may experience higher levels of anxiety and a lower sense of self-efficacy when facing challenges, which is typically manifested in difficulties with downregulating emotional reactivity to stressors (Galinsky, Gruenfeld, & Magee, 2003; Keltner et al, 2003). To illustrate this point, a few empirical studies have begun to document the relevance of perceived control for affective reactivity (Koffer et al, 2019; Tighe et al, 2015). Although there may be a link between perceived control and broad affective reactivity, the associations between control and NA reactivity are particularly strong.…”
Section: Perceived Control As a Link Between Ppr Affective Reactivitmentioning
confidence: 99%
“…As a consequence, they may experience higher levels of anxiety and a lower sense of self-efficacy when facing challenges, which is typically manifested in difficulties with downregulating emotional reactivity to stressors (Galinsky, Gruenfeld, & Magee, 2003; Keltner et al, 2003). To illustrate this point, a few empirical studies have begun to document the relevance of perceived control for affective reactivity (Koffer et al, 2019; Tighe et al, 2015). Although there may be a link between perceived control and broad affective reactivity, the associations between control and NA reactivity are particularly strong.…”
Section: Perceived Control As a Link Between Ppr Affective Reactivitmentioning
confidence: 99%
“…While it was unexpected that more disruptive behaviors did not predict greater distress reactivity, previous work aligns with this null finding 6 . It may be that some caregivers are using positive coping strategies such as mastery to mitigate distress when faced with disruptive behaviors 32 …”
Section: Discussionmentioning
confidence: 75%
“…Concerning the locus of control, even though items related to internal and external control which could diminish the capacity for adaptation were included, they did not form part of the final model. This may have been due to the perception of control and cause of events, although generating a stronger feeling of capacity for managing situations [ 22 , 26 ] may not be directly related to one’s possibility to adapt. That is, the capacity for adjusting to daily situations may be independent of the control that one feels one has over them.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, counting on strong perceived social support provides material sustenance and emotional comfort to people, in addition to helping them to reduce the negative evaluation of events, enabling them to alleviate distress and improve adaptation [ 45 ]. Along this line, the study by Koffer et al [ 26 ] found that beliefs about control in stressful situations increase with age, postulating that this result could be due to the decrease in availability and efficacy of psychosocial resources.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation